New species of little-known crickets from the subfamily Pteroplistinae (Orthoptera, Grylloidea) from Sabah and contribution to their bioacoustics - Tan, Ming Kai; Gorochov, Andrei; Japir, Razy; Chung, Arthur Y.c.; Robillard, Tony (Zootaxa, 2024)
Recent fieldwork in eastern Sabah led to the discovery of new little-known crickets from the subfamily Pteroplistinae (Orthoptera, Grylloidea). Three new species are described: Tembelingiola biaculeata sp. nov. and Tembelingiola kabili sp. nov. from Sepilok; Pteroplistes silam sp. nov. from Mount Silam. Previously, the calling song of only one species of Pteroplistinae was known. Here, the calling songs of the three new species, as well as that of Pteroplistes lagrecai Gorochov, 2004, are also described for the first time. Therefore, distinctive calling songs for five species and three genera of Pteroplistinae are presently known.